The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/rrq.498
|View full text |Cite
|
Sign up to set email alerts
|

Using Eye‐Tracking Measures to Predict Reading Comprehension

Abstract: This study examined the potential of eye-tracking as a tool for assessing reading comprehension. We administered three widely-used reading comprehension tests with varying task demands to 79 typical adult readers while monitoring their eye movements. In the York Assessment of Reading for Comprehension (YARC), participants were given passages of text to read silently, followed by comprehension questions. In the Gray Oral Reading Test (GORT-5), participants were given passages of text to read aloud, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 97 publications
0
1
0
Order By: Relevance
“…Analysis of readers' eye movements provides reading researchers with both a fine-grained, millisecond-bymillisecond level and a holistic, text-level view of reading processes (Mézière et al, 2023;Paulson, 2019). Information gained from the analysis of readers' eye movements has impacted reading theory for over a century (e.g., Huey, 1908Huey, /1968Jian, 2016;Rayner, 2009).…”
Section: Eye-movement Research On Readingmentioning
confidence: 99%
“…Analysis of readers' eye movements provides reading researchers with both a fine-grained, millisecond-bymillisecond level and a holistic, text-level view of reading processes (Mézière et al, 2023;Paulson, 2019). Information gained from the analysis of readers' eye movements has impacted reading theory for over a century (e.g., Huey, 1908Huey, /1968Jian, 2016;Rayner, 2009).…”
Section: Eye-movement Research On Readingmentioning
confidence: 99%
“…Eye-tracking (ET) has been explored as a less invasive and potentially more accurate method for assessing cognitive processes during reading compared to traditional methods like verbalizing thoughts (Pattemore & Gilabert, 2023;Sidhawara et al, 2023). Studies have shown that eye-tracking can provide valuable insights into how individuals engage with multimedia learning materials, revealing gender-based disparities in information processing preferences (Mézière et al, 2023). Additionally, research has demonstrated the effectiveness of eye-tracking in analyzing attention patterns of young individuals towards environmental advertising and journalistic texts, highlighting the cognitive effects of different media formats (Lobodenko et al, 2023;Saini et al, 2022).…”
Section: Introductionmentioning
confidence: 99%